Transformative Pedagogy: Investigating the Impact of Online Jigsaw Model on Motivation and Academic Achievement in High School Mathematics - Rizka Aliya Mitayani; Naufal Ishartono (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2024)
Several earlier research investigated the use of Jigsaw to improve the quality of the online mathematics teaching-learning process. However, few studies have used the Jigsaw approach to improve the quality of online mathematics education, particularly in terms of motivation and learning results. To address this research gap, the goal is to outline the process of integrating the Jigsaw model in online learning and to demonstrate the importance of enhancing student motivation during the learning process. This study used the classroom action research approach, which involved 36 students from a high school in Central Java Province, Indonesia. The results of this investigation indicate that the application of Jigsaw can be done online using numerous procedures indicated in this study. Furthermore, the results indicate a considerable improvement in motivation and learning outcomes. The findings of this study are expected to serve as a reference for teachers on how to implement the Jigsaw model online.